Study on the Genetic Differences in Reservoir Characteristics Based on the Bidirectional Provenance of the Yanchang Formation in the Jiyuan Area, Ordos Basin, China. (27th August 2022) - Tong, Qiang; Xia, Zhaohui; Huang, Jixin; Wu, Junchang; Wang, Yusheng; Meng, Zheng; Zhang, Chaoqian
Abstract : Ordos Basin is a Mesozoic sedimentary basin that underwent long-term evolution on the North China Craton. Many scholars have confirmed that in the Late Triassic, the basin was surrounded by ancient continents, and there were multiple provenance supply directions. Combined with the nature of the basement of the basin and the characteristics of the present structure, it is believed that the Jiyuan area is located in the central and western parts of the basin, spanning two first-level structural units, the Tianhuan Depression and the Yishan Ramp. This special geographical location makes Jiyuan area affected by bidirectional provenance. Controlled by the northwest and northeast depositional systems in the basin, Jiyuan area has accepted complex sedimentation and diagenesis, forming a low-porosity ultralow-permeability reservoir. However, the understanding of bidirectional provenance has been neglected in many previous studies on reservoir characteristics in the Jiyuan area. Therefore, the differential evolution of sedimentation and diagenesis caused by bidirectional provenance will cause serious deviations in the original understanding of reservoir characteristics in the Jiyuan area, which will inevitably affect subsequent exploration and development research work. In this paper, the mineral composition, physical properties, diagenesis, and diagenetic evolution of the Jiyuan area are studied by combining a large number of tests such as core physical properties, casting thin sections, scanning electron microscopy, cathodoluminescence, and X-ray diffraction. Then, the origins of reservoir development in two areas dominated by bidirectional provenance are analyzed and compared. Furthermore, the diagenetic facies are characterized by a cluster analysis of logging data, and finally, the reasons for the differences in reservoir distribution and the genetic mechanism between the Yinshan provenance area (YPA) and Alxa provenance area (APA) are obtained. The results show that, first, due to the different provenance, compared with the YPA, the reservoir pore space in the APA is better developed and the physical properties are better. Second, the clay mineral content and diagenesis are more important causes of reservoir differentiation, and the reservoir pores in the YPA are more affected by kaolinite and chlorite filling than those in the APA. Although more dissolution improvements have been obtained, the damage to the reservoir caused by cementation in the middle and late stages is extremely fatal, while the chlorite film in the APA reservoir has a better protection effect on the primary intergranular pores. Third, after the evolution of pores in the APA reservoir, more intergranular pores are preserved, and the distribution range of high-quality diagenetic facies is wider than that in the YPA. Finally, sedimentation is the basis for high-quality reservoir development, and good mineral content composition and favorable diagenetic transformation cause reservoir dissimilarity.